ACADEMIC LANGUAGE FUNCTIONS IN TEACHING CONTENT SUBJECTS - Mufidah, Salimatin; Rukmini, Dwi; Faridi, Abdurrahman (Language Circle: Journal of Language and Literature, 2012)
This study focuses on the use of academic language functions and the problems of their use in the process of teaching content subjects by using English as a means of instruction. Direct observation and recording were done to gather the data. Based on the overall data analysis and interpretation, the teachers have used academic language functions in English, but not all teachers use full-English in the teaching learning process. They applied academic language functions for the purpose of acquiring knowledge and skills. Furthermore, some teachers do not have adequate mastery of English because they just took a short English course. So, most content teachers sometimes find difficulties related to vocabulary/diction, grammar, pronunciation,ÃÂ  intonation and they often switched codes from English to Indonesian and vice versa. They have problems to express their idea in English due to their lack of vocabularies used and pronunciation. Therefore, it is suggested that content teachers himprove their competence especially in the classroom interaction using English.